Predictors of fresh organic fruits and vegetables consumption through intention of consumption / Nur Hazwani Mohammad Azam - Mohammad Azam, Nur Hazwani (2016)
Since the environmental awareness is increasing among the consumers, most of them decide to change their food consumption pattern to organic food. This trend had caused a lot of research and studies to be conducted to further understand the underlying factors that can lead to the behaviour. Theory of Planned Behaviour is a famous framework that had been used by researchers to understand factors that influence the intention and actual behaviour of organic consumption. There are also other factors that influence the intention and actual behaviour of organic consumption apart from the three main variables in Theory of Planned Behaviour (attitude, subjective norm and perceived behavioural control). This study applied the Theory of Planned Behaviour and added other independent variables (health awareness and personal norm) to find out the main factors that can predict the intention to consume fresh organic fruits and vegetables of the respondents who never consumed fresh organic fruits and vegetables before. It is found out that two independent variables from Theory of Planned Behaviour, subjective norm and perceived behavioural control are significantly influence the intention to consume fresh organic fruits and vegetables. One of the added variables, personal norm that represent environmental awareness is also found significant. It shows that the Theory of Planned Behaviour can be improved by adding personal norm to predict the intention to consume fresh organic fruits and vegetables among the consumers who never consumed fresh organic fruits and vegetables before.